Efficacy of coupled plasma filtration adsorption (CPFA) in patients with septic shock: A multicenter randomised controlled clinical trial. Issue 1 (8th January 2014) - Livigni, Sergio; Bertolini, Guido; Rossi, Carlotta; Ferrari, Fiorenza; Giardino, Michele; Pozzato, Marco; Remuzzi, Giuseppe
Abstract : Objectives: Coupled plasma filtration adsorption (CPFA, Bellco, Italy), to remove inflammatory mediators from blood, has been proposed as a novel treatment for septic shock. This multicenter, randomised, non-blinded trial compared CPFA with standard care in the treatment of critically ill patients with septic shock. Design: Prospective, multicenter, randomised, open-label, two parallel group and superiority clinical trial. Setting: 18 Italian adult, general, intensive care units (ICUs). Participants: Of the planned 330 adult patients with septic shock, 192 were randomised to either have CPFA added to the standard care, or not. The external monitoring committee excluded eight ineligible patients who were erroneously included. Interventions: CPFA was to be performed daily for 5 days, lasting at least 10 h/day. Primary and secondary outcome measures: The primary endpoint was mortality at discharge from the hospital at which the patient last stayed. Secondary endpoints were: 90-day mortality, new organ failures and ICU-free days within 30 days. Results: There was no statistical difference in hospital mortality (47.3% controls, 45.1% CPFA; p=0.76), nor in secondary endpoints, namely the occurrence of new organ failures (55.9% vs 56.0%; p=0.99) or free-ICU days during the first 30 days (6.8 vs 7.5; p=0.35). The study was terminated on the grounds of futility. Several patients randomised to CPFA were subsequently found to be undertreated. An a priori planned subgroup analysis showed those receiving a CPFA dose >0.18 L/kg/day had a lower mortality compared with controls (OR 0.36, 95% CI 0.13 to 0.99). Conclusions: CPFA did not reduce mortality in patients with septic shock, nor did it positively affect other important clinical outcomes. A subgroup analysis suggested that CPFA could reduce mortality, when a high volume of plasma is treated. Owing to the inherent potential biases of such a subgroup analysis, this result can only be viewed as a hypothesis generator and should be confirmed in future studies. ClinicalTrials.gov: NCT00332371; ISRCTN24534559 .